Биохимия моря: развитие, состояние, общие и прикладные задачи - (:unkn) unknown (My University, 1981)
Биохимия моря — молодая гибридная наука, развивающаяся на границе интересов ряда более зрелых научных дисциплин, в первую очередь биохимии организмов, экологии, геохимии и биогеохимии. Методология и методы ее — одновременно биохимические и экологические — испытывают на себе сильное влияние общенаучной системной методологии. Прикладные задачи биохимии моря сложились в контексте проблем загрязнения водной среды. Биохимия моря может стать теоретической основой для исследований в области самоочищения морских вод в природных условиях и искусственных очистных системах. Это междисциплинарное научное движение ведет к тому, что может быть названо общей биохимией, или биохимией живых и биокосных систем (в отличие от прежнего понимания общей биохимии как науки об обмене веществ у бактерий, растений, животных и человека). Биохимия моря — часть этого комплекса.
Marine biochemistry: the development, modern state and practical aspects
Marine biochemistry is the modern result of interscience development and interaction in which advanced organismic biochemistry, ecology, geochemistry and biogeochemistry are involved. The methodology and methods in marine biochemistry are both biochemical and ecological. At the same time, general systems theory and methodology influence marine biochemistry strongly, especially in the dynamic problems. Consequently, an analysis of complex ecobiochemical systems and interactions in them represents the main part of marine biochemistry both in poor science and practical aspects. Marine biochemistry becomes now the theoretical basis in solving pollution problems. Marine biochemistry is not the sole product of above mentioned interscience development; the most general problem for the near future is a formation of general biochemistry principles such as the synthesis (not the sum) of both organismic and ecological knowledge about metabolism in different biological systems from the cells to biosphere.